Business Acceleration for Youth Project - Nkhambule, Emily; Slane, David; Pierotti, Luca; Sheriff, Ramadhan Kadammanja (2025)
BUSINESS ACCELERATION FOR YOUTH PROJECT PROJECT OVERVIEW Alliance of Bioversity International and International Center for Tropical Agriculture (CIAT) is implementing the Business Acceleration for Youth project to reduce humanitarian assistance needs in Malawi’s resilience focus zones by accelerating youth-owned businesses. The project aims to accelerate and invest in youth-led enterprises to foster job creation, greater access to financing, diversified incomes, a more inclusive private sector and improved household resilience in targeted districts of Mangochi, Balaka, Machinga, Zomba, Chiradzulu, Chikwawa, Nsanje, Mulanje and Thyolo.